Pengaruh Biaya Operasional dan Perputaran Persediaan terhadap Laba Bersih - Asep Mulyana; Debora Tri Oktarina Pethy (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2018)
This study aims to determine how much influence the operational costs and inventory turnover on net income at PT Ultrajaya Milk Industry & Trading Company Tbk., both partially and simultaneously. The research method used is descriptive with a quantitative approach, while the statistical method used is multiple linear regression by first testing the classical assumptions using the SPSS V.25 program. The results of this study indicated that the data tested were standard with the results of the normality test using the Kolmogorov Smirnov (K-S) table and scatterplot, correlation coefficient tests. The data used in this study was taken from the company's annual financial report of PT Ultrajaya Milk Industry & Trading Company Tbk., for seven years, namely the period 2011-2017. It showed a very strong relationship, and partially operational costs affected net income, while inventory turnover did not affect net income. Also, simultaneously, operational costs and inventory turnover affected net income.